2021
DOI: 10.1063/5.0044519
|View full text |Cite
|
Sign up to set email alerts
|

Photochromism and influence of point defect charge states on optical absorption in aluminum nitride (AlN)

Abstract: In this work, we study the absorption properties of AlN in the range of 1.5 -5.5 eV, as well as the meta-stable change in absorption induced by ultraviolet (UV) irradiation (photochromism), and the restoration of the initial state under the action of irradiation of 2 -4 eV or elevated temperatures. UV irradiation results in a decrease of the absorption coefficient from 110 cm -1 to 55 cm -1 at 4.7 eV while in the visible range the absorption coefficient increases from values below 5 cm -1 to ~35 cm -1 . Measur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…[ 13,27,30 ] Absorption measurements have also confirmed the presence of carbon‐related defects in AlN. [ 17,31–33 ] Based on these studies, it has been determined that carbon is mainly a substitutional impurity on the nitrogen site in the n‐type material, with the possibility of complex formation with other carbon species. [ 31,33 ] However, recent results have shown that carbon occupies the metal site in semi‐insulating or p‐type material, so the site occupation depends on the dopant and can be manipulated by the Fermi level.…”
Section: Cn In Alganmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 13,27,30 ] Absorption measurements have also confirmed the presence of carbon‐related defects in AlN. [ 17,31–33 ] Based on these studies, it has been determined that carbon is mainly a substitutional impurity on the nitrogen site in the n‐type material, with the possibility of complex formation with other carbon species. [ 31,33 ] However, recent results have shown that carbon occupies the metal site in semi‐insulating or p‐type material, so the site occupation depends on the dopant and can be manipulated by the Fermi level.…”
Section: Cn In Alganmentioning
confidence: 99%
“…[17,[31][32][33] Based on these studies, it has been determined that carbon is mainly a substitutional impurity on the nitrogen site in the n-type material, with the possibility of complex formation with other carbon species. [31,33] However, recent results have shown that carbon occupies the metal site in semi-insulating or p-type material, so the site occupation depends on the dopant and can be manipulated by the Fermi level. [16,21,34] This identification and control of C configuration is important due to its impact on the electrical and optical properties.…”
Section: N In Alganmentioning
confidence: 99%